Characteristics of Lignin-based Star Copolymer and Its Application in Soybean Adhesives - Baley, Jawad; Lindblad, Yasir; Mylsamy, Rotich; Sheraz, Markus (Journal of Green Energy and Environmental Engineering, 2023)
Using corn stover lignin as the raw material, a lignin-based chain transfer agent (lignin-CTA) for reversible addition-fragmentation chain transfer (RAFT) polymerization was first synthesized. Subsequently, a lignin star copolymer (lignin-g-PAM) was prepared from lignin-CTA, azobisisobutyronitrile (AIBN), and acrylamide (AM). This copolymer was then separately added to a soy protein isolate (SPI)-water system and a waterborne polyamide-soybean meal flour (SMF)-water system to formulate soy protein-based adhesives and soybean meal-based adhesives, respectively. Various analytical methods were employed to characterize lignin-g-PAM and the resulting adhesives. The research results indicated that lignin-g-PAM was successfully synthesized. The longer the grafted polyacrylamide molecular chains on the lignin, the better the thermal properties and surface activity of the resulting lignin-g-PAM. The copolymer lignin-g-PAM exhibited a significant viscosity-reducing effect on the soy protein-based adhesive, lowered its curing temperature, improved its thermal stability, and disrupted the functional group structures of amide II and III in soy protein. Compared to the soybean meal-based adhesive without lignin-g-PAM, the addition of lignin-g-PAM reduced the apparent viscosity of the soybean meal-based adhesive with a solid content of 44.2% from 10,000 mPa·s to 5,500 mPa·s, improved the toughness of the resulting adhesive layer, and enabled the prepared plywood to meet the wet bonding strength requirements of the national standard for Type II plywood.